Industrial Separation Processes : Fundamentals. - Haan, André B. de (De Gruyter textbook., 2013)
Separation processes on an industrial scale comprise well over half of the capital and operating costs. They are basic knowledge in every chemical engineering and process engineering study. This book provides comprehensive and fundamental knowledge of university teaching in this discipline, exercises and solutions.